2011
DOI: 10.1002/app.35056
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of catalyzed polyimide/dicyanate semi‐interpenetrating networks for polymer gas membrane with suppressed CO2‐plasticization

Abstract: ABSTRACT:The work presents an approach to reduce the plasticization of polymeric membranes caused by condensable gases, and particularly the effect of plasticization caused on polyimides by CO 2 at high pressure. A technical polyimide, Matrimid V R , was chosen as a reference of polyimide membrane and the approach applied consisted of incorporating reactive oligomers to have cross-linkable mixed systems, which do not plasticize at high CO 2 pressure. Films of semi-interpenetrating networks (semi-IPNs) based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
2
2
0
Order By: Relevance
“…From the differential scanning calorimetry data, the glass‐transition temperature of the neat Matrimid was found to be 312.2 °C; this matched the literature value . (a), Moreover, all of the Matrimid–CNF composite showed glass‐transition temperatures near that of the pristine polymeric membrane (Table S1, Supporting Information, and Figure S) without any significant change. This showed that no chemical bonding was present between the CNFs and Matrimid in the Matrimid–CNF composites.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…From the differential scanning calorimetry data, the glass‐transition temperature of the neat Matrimid was found to be 312.2 °C; this matched the literature value . (a), Moreover, all of the Matrimid–CNF composite showed glass‐transition temperatures near that of the pristine polymeric membrane (Table S1, Supporting Information, and Figure S) without any significant change. This showed that no chemical bonding was present between the CNFs and Matrimid in the Matrimid–CNF composites.…”
Section: Resultssupporting
confidence: 84%
“…The mechanical properties of the Matrimid–CNF composite membranes were characterized by their Young's modulus, tensile stress, and extension at break values (Figure and Table S2, Supporting Information, ESI). The pristine Matrimid membrane showed nearly the same mechanical properties as reported earlier . However, the Matrimid–CNF composite membranes exhibited improvements in their mechanical properties with increasing CNF loading .…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Chemical structures of DCFT and DCFT-resin are shown in Figure 16. DCFT-modified membranes did not show any signs of plasticization in CO 2 feed pressures ranging from 1 to 30 atm [71]. Dicyanate cyclotrimerized into a uniform three-dimensional network of oxygen-linked triazine rings (cyanurate ester resin).…”
Section: Semi-interpenetrating Networkmentioning
confidence: 98%